Prevalence of Pressure Ulcers among patients in Ibn e Sina Hospital - Ayesha Fatima, Faiza Altaf, Muhammad Awais Hassan, Hamid Ali, Urooj Manzoor, Muhammad Daniyal Hayat, Asmar Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pressure is a localized injury to the skin and underlying tissue usually over a bony prominence, as a result of pressure, or pressure contributing to shear. Objective: The main objective was to determine the prevalence of pressure ulcers in the patients of Ibn e Sina hospital Multan and to determine the risk factors contributing to pressure ulcers by using Braden Scale. Methodology: It was a cross-sectional observational study conducted on 246 patients of Ibn e Sina hospital Multan. During the 6 months of the study, patients were interviewed regarding their demographics and risk factors for pressure ulcers according to the Braden scale. Spss21 was used to analyze the data. Results: Out of 246 patients, 74.8% of male patients had pressure ulcers. The patients were from 25 to 85 years old. The pressure ulcers were more frequent among the 45 to 65 years age group (i.e., 44.7%) and married patients (95.5%). Among 246 patients only 4.5% patients were at extra high risk and most of the patients were at low risk (69.5%) by using the Braden scale. This data will help physicians, researchers, and policymakers in Pakistan and other nations advocate for the needs of pressure ulcer patients. Conclusion: According to this study pressure ulcers were more frequent in male married patients of the middle age group. Most of the patients were at low risk of developing pressure ulcers on the Braden Scale. Keywords: Pressure ulcer PU, Pressure sores, Pressure Injuries, Prevalence, Risk factors, Braden Scale, Braden score, Hospitals, Intensive care units